Age model of a sediment core KX21-2 - Jiawang Wu; Zhifei Liu; Chao Zhou (PANGAEA, 2022)
The core KX21-2 collected on the Ontong Java Plateau (downcore profile over the past 380 ka).
In: Wu, J et al. (2022): Late Quaternary clay mineral assemblages in the Western Pacific Warm Pool [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.946134